EVALUATION OF BIOCHEMICAL CHARACTERISTICS OF A TRADITIONAL SALT FERMENTED FISH PRODUCT OF NORTHEAST INDIA WITH SPECIAL REFERENCE TO ITS FLAVOUR COMPONENTS - Majumdar, Ranendra Kumar; Basu, S.; Prasad, S. V. (Journal of Indian Fisheries Association, 2015)
"Lona ilish", is a traditional salt fermented fish product, widely consumed and very popular in Northeast part of India and Bangladesh. It is prepared exclusively from a high fat fish, Hilsa (Tenualosa) ilisha. "Lona ilish" was prepared in the laboratory following traditional process. After 150 days of fermentation, a better quality "lona ilish" was obtained. Biochemical characteristics of market sample was estimated and compared with the laboratory prepared one. A variation in biochemical composition was observed. Sensory quality of the final product of laboratory prepared "lona ilish" was compared with the market sample and found that the laboratory prepared product scored better than the market sample. The moisture (49.89%) and salt (15.48%) of the final product was found to be satisfactory for stability of the ’lona ilish’ at ambient temperature. Analysis of volatile compounds of "lona ilish" was done using GC-MS. It was concluded that, aldehydes, ketones and esters may possibly contribute characteristic aromas to the overall flavour of the salt fermented hilsa. Key words: hilsa, traditional technology, fermentation, salting, biochemical composition, volatile components